Ejecución presupuestaria del benemérito cuerpo de bomberos del Cantón Palenque en el periodo 2021. - Cabrera Burgos, Mirjana Annabell (2022)
The present case study work is directed to the budgetary execution of the meritorious Fire Department of the Palenque Canton in the period 2021, where budgetary information of the real and monetary resources of the institution is presented in the established period, which present a significant decrease compared to the initial remuneration, for which it is sought to determine the level of compliance through the use of efficiency and effectiveness indicators. Every year the fire brigade makes a budget where goals are proposed that at the end of the year it is intended to meet, therefore the budget becomes an extremely important instrument in the administration of resources, since it contributes to the economic planning of the institution with the sole purpose of anticipating needs and having available resources to deal with them effectively to consummate the achievements and goals. For the preparation of this document, budget management indicators were used to measure compliance with budget resources based on the total assigned within the determined period referring to the total executed.